2019
DOI: 10.1097/md.0000000000014046
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training as an adjunctive therapy to montelukast in children with mild asthma

Abstract: Background: This study investigated the effectiveness and safety of exercise training (ET) as an adjunctive therapy to montelukast for children with mild asthma (MA). Methods: A total of 72 children, ages 4 to 12 years with MA were randomly assigned to a treatment group or a control group at a ratio of 1:1. The subjects in the treatment group received ET plus montelukast, while the participants in the control group received montelukast alone. The primary endpoint was lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 27 publications
(27 reference statements)
0
23
0
1
Order By: Relevance
“…Basaran et al (30) indicated that changes in symptom scores significantly correlated with changes in total QoL scores, which was also reported by França-Pintoet al (42). Zhang et al (45) observed that asthmatics' wheezing, coughing, and sleep improved significantly in an exercise group. These reports found that regular aerobic exercise promotes the overall quality of life of asthmatic patients as demonstrated by physical fitness, asthma symptoms, and psychosocial factors (18,19).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Basaran et al (30) indicated that changes in symptom scores significantly correlated with changes in total QoL scores, which was also reported by França-Pintoet al (42). Zhang et al (45) observed that asthmatics' wheezing, coughing, and sleep improved significantly in an exercise group. These reports found that regular aerobic exercise promotes the overall quality of life of asthmatic patients as demonstrated by physical fitness, asthma symptoms, and psychosocial factors (18,19).…”
Section: Discussionmentioning
confidence: 57%
“…F E V 1 / F V C % w a s i n c l u d e d i n 7 a r t i c l e s (26,30,34,36,37,42,45) at the end of training programs, and a fixed-effects model revealed no effectiveness of aerobic exercise (I 2 =0.0%, WMD: 0.27, 95% CI: −0.43 to 0.98, P=0.443) (Figure 4).…”
Section: Fev1/fvc%mentioning
confidence: 99%
See 2 more Smart Citations
“…The main burden in asthma is reduced control manifesting as exacerbations. Importantly, children and young people with asthma perceive improvement in their asthma control and a reduction in asthma related symptoms following physical activity4–6 and report enjoyment and improved quality of life (QOL) from taking part in physical activity programmes 7. However, there is no clear evidence to support a correlation between QOL and the volume, intensity, or duration of the physical activity required to achieve improvement.…”
Section: Physical Activity and Asthmamentioning
confidence: 99%